Paradigm shift: uma aventura em busca do jogo - Souza, Jaderson Aparecido de (2011)
This study addresses the issue of the production of games and its scope as objects of knowledge and learning. Part of the current discussion is about theoretical elements of the games from the ontologically pragmatic assumptions of the metaphilosophy and of the general ontology of the metaverses and games. Methodologically, the production of a game is conceived as the production of a cultural and cognitive object which is organized according to the principles of the narrative designs, three-dimentional environments and characters integrated in the current cultural movement of the digital natives. It is discussed the relation among the methodological assumptions of the approach of the new technologies, the narratology and playful and the current educational reflections that take the games as cognitive objects. It approaches the production contexts of a game, focusing the hypermedia research areas which show the games as cultural agents that promote the human creativity and freedom in the digital era, its relevance as playfulness sense producer and as horizons of knowledge production. It resumes the discussion of the use of games in the educational process confronting them with the entertainment issues and the scientific research that uses the new technologies. It locates and delineates the methodological parameters and conceptual limits for the production of a game which has concepts as objects. It proposes the normative structure of a game design document, its parameter and its development in a high fidelity digital phototype. It culminates in the perspective of the games complexities as digital and cultural objects that locates in the horizons among art, ethics and science, fundamental to the development of the postmodern culture